E-Procurement and Innovation in the Portuguese Municipalities: When Change Is Mandatory - Soares, Luís (2016)
Changing the traditional pattern of public procurement for an electronic paradigm is a radical innovation involving major organizational changes, the breaking up of traditional processes and practices, obsolescence of knowledge and skills. Going beyond the European Commission's recommendations, in 2009 Portugal pioneered in making e-procurement mandatory in the pre-award phase, in a European context of multiple technical standards and lack of interoperability of electronic platforms across the EU countries. Six years later, when the creation of a European e-procurement single market is a EU mission and a major legislative amendment is underway in Portugal, this study looks at the relationship between e-procurement and innovation in the Portuguese municipalities aiming to understand the extent into which the adoption of e-procurement embraced a real organizational change or, on the other hand, if it just represented a mere adaptation of the usual procurement practices. The study draws on data from an electronic survey to all municipalities in mainland Portugal and the analysis is mainly descriptive and exploratory. The paradigm shift in public procurement involves major organizational changes but, overall, the results suggest that most municipalities do not have a clear understanding of the innovative scope (depth and diversity) implied by e-procurement. E-procurement shows advantages over the paper-based model but an unbalanced perception of the innovation dimensions has influenced the implementation of e-procurement and the degree of organizational change.